2014
DOI: 10.1590/1516-3180.2013.7740026
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective body hypothermia among newborns with hypoxic ischemic encephalopathy: three-year experience in a tertiary university hospital. A retrospective observational study

Abstract: Neuroprotective body hypothermia among newborns with hypoxic ischemic encephalopathy: three-year experience in a tertiary university hospital. A retrospective observational study Hipotermia corpórea neuroprotetora em recém-nascidos com encefalopatia hipóxico-isquêmica: três anos de experiência em hospital universitário terciário. Um estudo observacional retrospectivo ABSTRACTCONTEXT AND OBJECTIVE: Neonatal hypoxic-ischemic encephalopathy is associated with high morbidity and mortality. Studies have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…[ 7 , 8 ] The neuroprotective strategy of therapeutic hypothermia involves the modulation of inflammatory cascade inhibition, reduced production of reactive oxygen species, and a reduction in metabolic rate. [ 9 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 8 ] The neuroprotective strategy of therapeutic hypothermia involves the modulation of inflammatory cascade inhibition, reduced production of reactive oxygen species, and a reduction in metabolic rate. [ 9 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…This study describes 8 years of experience with the use of ice packs in whole body TH in newborns with HIE in a Tertiary University Hospital in Brazil (Magalhães et al, 2014). In a national survey, using social media, on the use of TH, it was observed that 38% of 411 health care professionals surveyed reported not using this therapy in HIE at the neonatal units they work at.…”
Section: Discussionmentioning
confidence: 99%
“…However, the safety and effectiveness of TH in low‐ and middle‐income countries still unknown (Pauliah, Shankaran, Wade, Cady, & Thayyil, 2013), especially with the use of alternative devices for cooling, such as ice packs, cold water bottles, mattresses made of phase change materials and low‐cost servo‐controlled cooling blankets (Prashantha et al, 2019; Robertson et al, 2008; Rossouw, Irlam, & Horn, 2015; Thomas et al, 2011). The Neonatology Service of Santa Casa de São Paulo started the whole‐body cooling program in newborns with HIE using ice packs in 2009 (Magalhães et al, 2014). The primary objective of this study was to evaluate the feasibility and effectiveness of using low‐cost devices (ice packs) to reach and maintain the TH target temperature in newborns with moderate or severe HIE using low‐cost devices in a limited resource setting, by analyzing the rectal temperature curves during the cooling period.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] En estudios previos, la elevación de la aminotransferasa de alanina en el recién nacido ha demostrado una alta especificidad para predecir el riesgo de encefalopatía hipóxico-isquémica, mientras que un incremento en la lactato deshidrogenasa resulta un marcador altamente sensible para daño celular. [15][16][17] El incremento en las concentraciones séricas de estas enzimas, así como sus patrones diferenciados de aclaramiento en plasma, pueden servir como marcadores predictivos de encefalopatía hipóxico-isquémica en neonatos con signos de sufrimiento fetal en el periparto. 1,[15][16][17] La importancia de establecer el diagnóstico oportuno de la asfixia neonatal radica en la posibilidad de efectuar ciertos procedimientos terapéuticos que reducen la probabilidad de que el neonato tenga secuelas neurológicas, en particular la hipotermia terapéutica; sin embargo, las ventajas neuroprotectoras de esta medida disminuyen rápidamente si se retrasa su aplicación, solo habiéndose demostrado ventaja si se inicia en las 6 horas posteriores al evento de asfixia.…”
Section: Introductionunclassified
“…[15][16][17] El incremento en las concentraciones séricas de estas enzimas, así como sus patrones diferenciados de aclaramiento en plasma, pueden servir como marcadores predictivos de encefalopatía hipóxico-isquémica en neonatos con signos de sufrimiento fetal en el periparto. 1,[15][16][17] La importancia de establecer el diagnóstico oportuno de la asfixia neonatal radica en la posibilidad de efectuar ciertos procedimientos terapéuticos que reducen la probabilidad de que el neonato tenga secuelas neurológicas, en particular la hipotermia terapéutica; sin embargo, las ventajas neuroprotectoras de esta medida disminuyen rápidamente si se retrasa su aplicación, solo habiéndose demostrado ventaja si se inicia en las 6 horas posteriores al evento de asfixia. [17][18][19][20][21][22][23] El objetivo del estudio fue: analizar la posible asociación entre el cambio en los valores séricos de lactato deshidrogenasa con respecto a distintos intervalos en las primeras 12 horas de vida extrauterina y la encefalopatía hipóxicoisquémica en recién nacidos con factores de riesgo para asfixia neonatal.…”
Section: Introductionunclassified